Transformation of Platform Governance in China The Politics of Technology Routes - Jiang, Yuhao; Jia, Kai. (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
The admiration of science and technology and the emphasis on political stability are two sides of the same coin in China. Therefore, China is more likely to take aggressive measures to promote or inhibit platform development than the United States and the European Union. But the uncertainty in the decision-making process is worrisome and calls for a broader discussion of the multiple political consequences of technology. Yuhao Jiang is a researcher at the Institute of Public Policy at South China University of Technology. He is a doctor of the Chinese Academy of Social Sciences. Professor Yuhao was a postdoctoral fellow at the School of Public Administration, Tsinghua University, and a visiting scholar at the European University Institute in Italy. Yuhao Jiang's research interests include digital governance, Chinese science and technology policy, techno-politics, and Chinese political economy. He has published books such as "Mutiple Modernities and Critical Jurisprudence" and "Deliberative Democracy and Orderly Participation. Kai Jia is an associate professor in the School of International and Public Affairs, Shanghai Jiaotong University. He is also a researcher in the Center for Industrial Development and Environmental Governance of Tsinghua University. Dr. Kai is the Fulbright Scholar, visiting scholar in UC Davis, ETLA (Helsinki) and EBS(Tallinn). The research interests of Kai Jia mainly lie in the intersection between digital technology and public policy, covering issues like Governance of AI and Blockchain, Digital Economy, Digital Government, Global Digital Governance, etc.
Chapter 1: Introduction -- Part I: Rise of Digital Platform and Its Transformative Possibilities -- Chapter 2: A Brief History of Evolution of Platform-based Internet -- Chapter 3: Analysis of Platform Economic Logic: Structure and Its Future -- Chapter 4: Rethinking Platform-based Internet: Possibilities of New Technology Routes -- Chapter 5: Global Governance of Transnational Digital Platforms -- Part II: Path to Reforming Platform Governance in Chinese Context -- Chapter 6: Technology, Governance and Politics: the Ideological Foundation of Platform Governance in China -- Chapter 7: Choice of Technology Routes as a National Responsibility: Change in Chinese context? -- Chapter 8: Change in Mechanism of Public Decision-making Responsibility: Blockchain Technology and Break out of 'Command-and-Control' -- Chapter 9: Construction of Responsible Government through 'Collaboration -and- Sharing' Mechanism -- Chapter 10: Innovation in Management Mechanism of Big Data for Government Affairs: From 'Command-and-Control' to 'Collaboration-and-Sharing' -- Chapter 11: Asset-based Management of Government Data: Design in the Context of the 'Collaboration-and-Sharing' Mechanism -- Chapter 12: Public Choice in Artificial Intelligence Governance Policy: Toward 'Shared Freedom'.
Keywords: Asia -- Politics and government; Crime; Technology; Asia -- Economic conditions; Asian Politics; Crime and Technology; Asian Economics